Prevalence of neutropenia in US residents: a population based analysis of NHANES 2011-2018 - Jing Zhou; Nan Zhou; Qing Liu; Zhi-Ping Xie; Yun Xu; Si-Cheng Dai; Juan Lu; Zheng-Yang Bao; Li-Da Wu (BMC, 2023)
Abstract Aims Neutrophils play a pivotal in immunity and inflammation. We aim to investigate the prevalence of neutropenia in the United States. Methods In this cross-sectional study, participants from the National Health and Nutrition Examination Survey (NHANES) (2011-2018) were enrolled. Demographic information, hematologic measurements, smoking status of all participants were collected for all participants. All statistical analyses were performed utilizing the NHANES survey weights. Covariate-adjusted linear regression was used to compare hematologic indices in different population grouped by age, sex, ethnicity, and smoking. We also employed multivariate-logistic regression to estimate the weighted odds ratio with a 95% confidence interval and predict the neutropenia risk among. Results 32,102 participants from NHANES survey were included, represented 286.6 million multiracial population in the United States. Black participants had lower mean leukocyte count (mean difference (MD): 0.71 × 109/L; P < 0.001) and lower neutrophil count (MD: 0.83 × 109/L; P < 0.001) compared with white participants after adjusting for age and sex. Furthermore, t a notable observation was the significant downward shift in the distribution curves of leukocyte count and neutrophil count among black participants. Smokers had a higher mean leukocyte count (MD: 1.10 × 109 cells/L; P < 0.001) and a higher mean neutrophil count (MD: 0.75 × 109 cells/L; P < 0.001) comparing with nonsmokers. The estimated prevalence of neutropenia was 1.24% (95% CI: 1.11 − 1.37%), which corresponds to approximately 35.5 million individuals in the United States. The prevalence of neutropenia in black participants was significantly higher than other races. Results of logistic regression analysis showed that black individuals, male individuals, and children younger than 5 years had a higher risk of neutropenia. Conclusions Neutropenia is more common in the general population than we thought, especially in black individuals and children. More attention should be paid to neutropenia.